2019
DOI: 10.1155/2019/1318639
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Factors Influencing the Efficiency of Acupuncture in Tinnitus Patients

Abstract: An effective acupuncture treatment must comprehend the influence of various factors, but studies in this aspect remain limited. This study aimed to identify relevant factors and search for the best practical method of acupuncture for patients with tinnitus. The study was a retrospective review of patients’ data with a prospective design who had subjective idiopathic tinnitus and received acupuncture between May 2012 and August 2017. Patients’ demographics, tinnitus characteristics, previous diseases, underlyin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 35 publications
0
5
0
Order By: Relevance
“…Both studies re-ported a significant improvement of TSi and VASTL [17,20]. Consistently, with the application of MAC on periauricular and distal acupoints, another 2 studies demonstrated more VASTL improvement (with a high statistically significant difference) [18,19] than with the application of MAC on periauricular acupoints only [27]. Again, in another research that compared acupuncture, western medicine, and Chinese herbs, acupuncture produced the greatest positive significant effect on tinnitus [28].…”
Section: Discussionmentioning
confidence: 73%
“…Both studies re-ported a significant improvement of TSi and VASTL [17,20]. Consistently, with the application of MAC on periauricular and distal acupoints, another 2 studies demonstrated more VASTL improvement (with a high statistically significant difference) [18,19] than with the application of MAC on periauricular acupoints only [27]. Again, in another research that compared acupuncture, western medicine, and Chinese herbs, acupuncture produced the greatest positive significant effect on tinnitus [28].…”
Section: Discussionmentioning
confidence: 73%
“…In this study, we applied acupuncture to the most possible acupoints around the ear and the body overall. Our application pattern is supported by a recent study that recommended stimulating the largest possible number of acupoints around the ear or in various parts of the body to achieve the desired outcome from the application of AT in patients with tinnitus [40].…”
Section: Discussionmentioning
confidence: 76%
“…The frequency of acupuncture is often a cause of concern. Studies have assessed the effective number of acupuncture sessions for conditions, such as migraines [ 14 ], chronic pelvic pain syndrome [ 15 ], stroke [ 16 ], and tinnitus [ 17 ]. In Japan, acupuncture is traditionally performed once a week, and our clinic often follows this schedule.…”
Section: Discussionmentioning
confidence: 99%